(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
Against the backdrop of Nigeria’s seismic activity, which has been clearly scientifically proven to have increased over the past 35 years, seismic activity in northern Nigeria is becoming alarming. (Abuja 2018, Ifewara 2019, Mpape Abuja 2024, and Yola 1984-2005 all) demonstrate that Nigeria has entered a seismic zone. Northern Nigeria has had more than 17 events between 1990 and 2018, indicating an increase in seismicity. Over time, this has grown, reaching roughly 20 in 2024.The oceanic and continental fracture system and the NNE-SSW trending Ifewara - Zungeru fault zone are clearly linked by geophysical investigations of historical and instrumental seismicity in northern Nigeria. The study focusses on northern Nigeria’s seismology and the active fault line that causes tremors in the region.